Reducing the public speaking anxiety of ESL college students through Popsispeak - Pontillas, Marlon S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
It is evident that even students had already English subjects in the primary and secondary years, some of them are afraid to use the English language in the classroom in the tertiary level. They find difficulty in expressing themselves using the said language because of several factors. This study focuses on helping the students face their fear in public speaking, which interferes their oral communication skills. The teacher-researcher introduced an intervention called Popsispeak. This study utilized a one-shot case study. A total of 28 students of Camarines Sur Polytechnic Colleges who were enrolled in the class of the teacher-researcher for the A.Y. 2017-2018 2nd semester served as the respondents of the study. T-test for Dependent Samples was used to determine the significant difference between the pre-test and post-test results of the students’ Personal Report of Public Speaking Anxiety (PRPSA) devised by McCroskey. The same statistical tool was also used in determining the level of oral communication skills of the students before and after the intervention. Pearson’s Correlation was used in determining the relationship between public speaking anxiety and oral communication skills. Also, thematic analysis was utilized in grouping the responses of the students regarding their experiences in the intervention activity. It was found out that Popsispeak is an effective intervention in helping students elevate their oral communication skills and reduce their public speaking anxiety.